Performative Writing as a Method of Inquiry With the Material World: The Art of the Imperative (LEARNing Landscapes, 2020)
Understanding writing as a performative material practice, this paper highlights the “imperative” as a strategy to enhance writing practices in our classrooms and academic workshops. Drawing on posthuman theories and intra-active relationships, it describes how performative arts-based writing can provide a way to engage with the human and nonhuman, the embodied, sensory elements of our writerly worlds. Employing a critical collaborative autoethnographic methodology, the two authors provide a narrative account of a year as two research Fellows in a university exploring writing as a method of inquiry through designing and implementing a series of performative arts-based writing activities.
Keywords: performative writing; imperative; posthuman; intra-action; arts-based